Mentoring of Opak Samiler MSMEs towards SDG's 9 Indonesia based on lean tools - Indah Apriliana Sari; Rahmah Utami Budiandari; Satrio Sudarso; Fajar Sulastri; Fitriyah Nur Indahsari (Universitas Muhammadiyah Magelang, 2024)
The Opak Samiler business group in Wonosunyo Village uses manual production methods, resulting in low productivity only 3 kg of dry opak per day, produced only in their free time after fieldwork. The lengthy and skill-intensive dough flattening process, along with uneven opak thickness, frequently receives consumer complaints. High demand, particularly during Eid al-Fitr, is difficult to meet due to limited production capacity and weather conditions. Therefore, this community service project aimed to increase the business group's productivity by implementing Lean Tools-based work aids: a mechanical samiler printer and a drying machine. The implementation involved socializing and training the business group members on tool use, and evaluating the production process post-implementation. Consequently, these work aids increased productivity by up to 65% compared to conventional methods.